THE IMPACT OF FOREIGN ECONOMIC RELATIONS ON THE DEVELOPMENT OF TOURISM - Nurfayzieva Mokhinur Zayniddinovna (Modern American Journals, 2025)
This paper examines the role of foreign economic relations in shaping the development of the tourism sector. As globalization accelerates, international trade, foreign direct investment (FDI), diplomatic cooperation, and cross-border agreements have become essential tools for enhancing the competitiveness and sustainability of tourism destinations. The study explores how foreign partnerships contribute to tourism infrastructure development, facilitate market access, improve service quality, and promote international mobility through visa liberalization and transport agreements. By analyzing global and regional examples, the paper highlights the strategic importance of integrating tourism policies with broader economic diplomacy and trade strategies. The findings suggest that well-structured foreign economic relations not only attract international tourists but also create long-term benefits for local communities and national economies.
Keywords: Tourism development, foreign economic relations, FDI, international cooperation, globalization, sustainable tourism.